Anti-Social Behavior Policy in England and Wales - Radulović, Ljiljana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
This article is focused on recent legislation in the UK dealing with the problem of anti- social behavior. This problem has been one of the central policy preoccupations of government in the last few decades. The new approach presented in the Anti-Social Behaviour Act emphasised the fundamental importance of community and citizen participation and involvement in the policy of reducing anti-social behaviour. There is 1. Political and 2. Legal context: 1. increasing public confidence in the criminal justice system and reducing fear of crime, redistributing power from the state to society, from the centre to local communities, giving people the opportunity to take more control over their lives in connection and collaboration with public services. 2. Improve Community justice principles /community crime prevention, community policing, community courts, restorative justice sanctioning systems, citizen reparative boards, et. cet./.